Job commitment and its impact on job performance: An applied study on the branch of Ministry of Islamic Affairs, Dawah and Guidance in Asir region - Al- Khudairi, Khudair Suleiman; Al- Ariqi, Bassim Qaid (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aims to identify the concept and importance of job commitment and job performance with a particular focus on the common job commitment level in Asser. It also figures out the relationship between job commitment and job performance in the Asser. The study uses the analytical descriptive approach as a methodology and reached some results as follows; the indicators of job commitment including days of attendance, days of absence, number of staff, number of appointed staff, number of transferred employees, turnover rate of transferred staff and turnover rate of new hire on job performance represented in the number of training programs for the staff of the division of Ministry of Islamic Affairs, Dinah and Guidance in Asser. The impact percentage reached 98% while the other 2% goes to other factors and indicators not mentioned in this study. The results also show that there is an impact to the statistically significant indicators of job commitment to the number of training programs. For example, days of attendance comes in the first rank follows by the turnover rate of transferred staff in the second rank. The number of transferred staff comes in the third rank follows by the turnover rate of new hire in the fourth rank. The number of appointed staff comes in the fifth rank followed by the number of employees and days of absence respectively. The study suggested some recommendations including the necessity to link the concept of job commitment to measurements and practices to be well designed and to be well integrated with the system of incentives, censorship and employment. It also recommended that administrative leadership should improve the job commitment of their staff through providing a regulatory environment that allows job creativity.